2023
DOI: 10.1007/978-3-031-28486-1_21
|View full text |Cite
|
Sign up to set email alerts
|

A Second Look at DNS QNAME Minimization

Abstract: The Domain Name System (DNS) is a critical Internet infrastructure that translates human-readable domain names to IP addresses. It was originally designed over 35 years ago and multiple enhancements have since then been made, in particular to make DNS lookups more secure and privacy preserving. Query name minimization () was initially introduced in 2016 to limit the exposure of queries sent across DNS and thereby enhance privacy. In this paper, we take a look at the adoption of , building upon and extending m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For example, instead of querying the root DNS servers for time.apple.com (which the roots cannot directly answer, they can only point to where the .com authoritative servers), a recursive resolver using qname minimization will only query the root for .com, hiding the full name. While study has shown that qname minimization is still not widespread [17], its use is growing [42]. Our method applies only to resolvers that do not use qname minimization.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, instead of querying the root DNS servers for time.apple.com (which the roots cannot directly answer, they can only point to where the .com authoritative servers), a recursive resolver using qname minimization will only query the root for .com, hiding the full name. While study has shown that qname minimization is still not widespread [17], its use is growing [42]. Our method applies only to resolvers that do not use qname minimization.…”
Section: Limitationsmentioning
confidence: 99%